Vegetation restoration of abandoned cropland improves soil ecosystem multifunctionality through alleviating nitrogen-limitation in the China Danxia - Wang, Chao; Yang, Qiannan; Zhang, Chi; Zhang, Xiaolong; Chen, Jing; Liu, Kexue (Frontiers in Plant Science, 2023)
The microbial requirement for nutrient resources can be estimated by soil extracellular enzyme activities (EEA) and their stoichiometries. Implementing the Grain for Green Program has significantly impacted land use and soil nutrient management in the China Danxia. However, it’s unclear how vegetation restoration in this area changes the microbial nutrient limitation in terms of soil EES. We explored EEA and EES under vegetation restoration types (naturally restored secondary forests (NF) and artificially planted forests (AF)) on abandoned cropland for better understanding microbial nutrient limitation in the China Danxia. Both NF and AF soils averaged higher C- and P- acquiring enzyme, indicating rapid C and P turnover rates after vegetation restoration. However, vegetation restoration resulted in higher C requirement for microorganisms with higher enzyme C:N and vector length. In addition, microorganisms shifted from N- (< 45°) to P-limited (> 45°) conditions with enzyme N:P less than 1 after vegetation restoration, and NF exacerbated microbial P limitation compared to AF. Decreased N limitation following vegetation restoration could be contributed to improving soil ecosystem multifunctionality. The greater variation of EES was explained by the interaction of pH, soil nutrient, and microbial biomass than by any one of these factors alone, suggesting that both abiotic and biotic factors regulate microbial nutrient limitation. Overall, our results reveal NF-type restoration is an important approach to alleviate N limitation and enhance soil ecosystem, and provide insight into nutrient management strategies under ecological restoration of degraded areas.